Initial recommendations for higher‐tier risk assessment protocols for bumble bees, Bombus spp. (Hymenoptera: Apidae). (8th September 2015) - Cabrera, Ana R; Almanza, Maria Teresa; Cutler, G Christopher; Fischer, David L; Hinarejos, Silvia; Lewis, Gavin; Nigro, Daniel; Olmstead, Allen; Overmyer, Jay; Potter, Daniel A; Raine, Nigel E; Stanley‐Stahr, Cory; et al.
ABSTRACT: Global declines of bumble bees and other pollinator populations are of concern because of their critical role for crop production and maintenance of wild plant biodiversity. Although the consensus among scientists is that the interaction of many factors, including habitat loss, forage scarcity, diseases, parasites, and pesticides, potentially plays a role in causing these declines, pesticides have received considerable attention and scrutiny. In response, regulatory agencies have introduced more stringent pollinator testing requirements for registration and reregistration of pesticides, to ensure that the risks to pollinators are minimized. In this context, guidelines for testing bumble bees ( Bombus spp.) in regulatory studies are not yet available, and a pressing need exists to develop suitable protocols for routine higher‐tier studies with these non‐ Apis sp., social bees. To meet this need, Bayer CropScience LP, Syngenta Crop Protection LLC US, and Valent USA. Corporation organized a workshop bringing together a group of global experts on bumble bee behavior, ecology, and ecotoxicology to discuss and develop draft protocols for both semi‐field (Tier II) and field (Tier III) studies. The workshop was held May 8–9, 2014, at the Bayer Bee Care Center, North Carolina, USA. The participants represented academic, consulting, and industry scientists from Europe, Canada, the United States, and Brazil. The workshop identified a clear protection goal and generated proposals for basic experimental designs, relevant measurements, and endpoints for both semifield (tunnel) and field tests. These initial recommendations are intended to form the basis of discussions to help advance the development of appropriate protocol guidelines. Integr Environ Assess Manag 2016;12:222–229. © 2015 The Authors. Integrated Environmental Assessment and Management Published by SETAC Key Points: Initial recommendations for semifield and field studies with bumble bees based on expert opinions. Identification of a protection goal and relevant endpoints for risk assessment of pesticides to bumble bees. Identification of research needs to advance the development of guidelines for bumble bee regulatory testing.